2012
DOI: 10.4161/onci.19334
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a G-CSF-Granulocytic MDSC axis that promotes tumor progression

Abstract: Myeloid-derived suppressor cells (MDSC) induced during neoplasia display potent pro-tumorigenic activities. Tumor-derived factors influence MDSC development, yielding monocytic and granulocytic subsets. In contrast to monocytic MDSC, little is known about how granulocytic MDSC develop. We demonstrated that tumor-derived G-CSF drives granulocytic MDSC formation, thus providing new insights into myeloid-tumor biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 10 publications
1
39
0
Order By: Relevance
“…Moreover, when CAIX levels are diminished within the primary tumor, circulating G-CSF levels are near those observed in na€ ve mice, resulting in a concomitant reduction in G-MDSC detected in the lung. On the basis of our observations identifying reduced plasma G-CSF in mice with CAIX-depleted tumors, it is likely that the observed CAIX-G-CSF axis is one mode by which CAIX activity promotes the metastasis of hypoxic breast cancers, by influencing the G-CSF-granulocytic MDSC axis (44). These important findings are our contribution to this field.…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, when CAIX levels are diminished within the primary tumor, circulating G-CSF levels are near those observed in na€ ve mice, resulting in a concomitant reduction in G-MDSC detected in the lung. On the basis of our observations identifying reduced plasma G-CSF in mice with CAIX-depleted tumors, it is likely that the observed CAIX-G-CSF axis is one mode by which CAIX activity promotes the metastasis of hypoxic breast cancers, by influencing the G-CSF-granulocytic MDSC axis (44). These important findings are our contribution to this field.…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, tumor-secreted G-CSF that contributes to neutrophil mobilization, activation and stimulation of oxidative metabolism [188][189][190][191], is also involved in the polarization towards immunosuppressive MDSCs [192,193]. The presence of G-MDSCs was shown to be important for promoting tumor growth [193].…”
Section: Regulation Of Neutrophil Mobilization Recruitment and Activmentioning
confidence: 99%
“…It was revealed that tumor-induced granulocyte colony-stimulating factor (G-CSF) is one of those factors (Waight et al 2011;Abrams and Waight 2012;Luyckx et al 2012;Kawano et al 2015). Our recent study also showed that the serum G-CSF level is associated with the inhibition of expansion and differentiation of G-MDSCs in tumor-bearing adiponectin knockout mice (Han et al 2013).…”
Section: The Subsets Of Mdscsmentioning
confidence: 86%
“…Recently, fibrocytic MDSCs (F-MDSCs) are characterized as a novel MDSC subset in human (Abrams and Waight 2012;Zhang et al 2013;Mazza et al 2014;Zoso et al 2014;Gunaydin et al 2015). F-MDSCs show tumorassociated circulating fibrocyte phenotypes and have T cell-mediated immunosuppressive functions.…”
Section: The Subsets Of Mdscsmentioning
confidence: 99%